Neurotoxicity and Developmental Disabilities - Davidson, Philip William, 1941-2022; Myers, Gary J.; Weiss, Bernard (International review of research in mental retardation, 2006)
Neurotoxicity and Developmental Disabilities is a comprehensive review of the relationship between neurotoxicity and mental retardation. Though individual chapters each focus on a specific toxin, the chapters jointly emphasize that many variables influence the developmental outcomes following exposure to neurotoxicants, including timing of exposure, pattern of exposure, dose, susceptibility, and environmental conditions. Coverage includes the developmental consequences of maternal exposure to methyl mercury, and direct exposure to PCBs and Dioxins, lead, methanol, parental smoking, pthalates and pesticides. Additional chapters review research on environmental agents and autism, and assessment studies of exposure. This thematic volume in the International Review of Research in Mental Retardation begins with forewords by Stephen R. Schroeder, and series editor Laraine Glidden.